2018
DOI: 10.1002/clc.23027
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a defined, plant‐based diet reduces lipoprotein(a), inflammation, and other atherogenic lipoproteins and particles within 4 weeks

Abstract: A defined, plant-based diet has a favorable impact on Lp(a), inflammatory indicators, and other atherogenic lipoproteins and particles. Lp(a) concentration was previously thought to be only minimally altered by dietary interventions. In this protocol however, a defined plant-based diet was shown to substantially reduce this biomarker. Further investigation is required to elucidate the specific mechanisms that contribute to the reductions in Lp(a) concentrations, which may include alterations in gene expression. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 43 publications
1
40
1
Order By: Relevance
“…Fibrinogen synthesis is triggered by the ingestion of a meal [ 39 ]. Westernized diet increases [ 40 ] and plant-based diet reduces serum fibrinogen levels [ 41 ]. However, in the present study there was no significant change in the fibrinogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen synthesis is triggered by the ingestion of a meal [ 39 ]. Westernized diet increases [ 40 ] and plant-based diet reduces serum fibrinogen levels [ 41 ]. However, in the present study there was no significant change in the fibrinogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that consuming a properly composed diet has been associated with better health status, due to the protective effect against various chronic diseases [ 37 , 45 ]. Evidence regarding the role of diet quality on glucose and lipid metabolism and inflammatory markers has been established in multiple observational studies [ 45 , 46 , 47 , 48 , 49 ]. The authors reported that a plant-based pattern and the Mediterranean diet (characterized by a high consumption of vegetables, fruits, legumes, olive oil, and low consumption of red meats) are associated with favorable health status and less inflammation [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Screening for increases in Lp(a) levels in the general population is still not recommended [11]. Because the majority of circulating Lp(a) molecules are genetically determined with little effect from diet and environment [196] and because plasma concentrations do not vary considerably around a preset baseline over a lifespan (<10%) in any individual, it is ere is an inverse relationship between weight plasma Lp(a) concentration and obesity [63] Diet Majority of the reports have shown no to minimum reduction [181]; however, a defined plant-based diet [182] and fish oils were found to reduce plasma Lp(a) by 10% [180] Journal of Lipids 14…”
Section: Diet and Physical Exercisementioning
confidence: 99%
“…In four phase III trials, 382 participants receiving maximally tolerated serum Lp(a) concentration is regulated independently of diet, other lipoprotein classes, and long-term or acute rigorous physical exercise [13,181], despite these activities producing a favorably improved lipid profile [13,199]. Conversely, a recent study has shown that a plant-based diet substantially decreased inflammatory biomarkers and atherogenic lipoproteins, including Lp(a) [182].…”
Section: Reducing the Production Of Novel Lp(a) (1)mentioning
confidence: 99%